2023
DOI: 10.1093/cercor/bhad070
|View full text |Cite
|
Sign up to set email alerts
|

Anodal transcranial direct current stimulation enhances ankle force control and modulates the beta-band activity of the sensorimotor cortex

Abstract: This study aimed to investigate the cortical responses to the ankle force control and the mechanism underlying changes in ankle force control task induced by transcranial direct current stimulation (tDCS). Sixteen young adults were recruited, and they completed the electroencephalogram (EEG) assessment and high-definition tDCS (HD-tDCS) sessions. Root mean square (RMS) error was used to evaluate ankle force control task performance. Spectral power analysis was conducted to extract the average power spectral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Appropriate force control of the ankle requires the proper functioning of baroreceptors and the regulation of cortical networks of the brain [ 51 ]. A single session of HD-tDCS applied over SM1 enhanced force control by modulating the beta-band activity of the sensorimotor cortex [ 23 ]. Moreover, tDCS can modulate cortical excitability to influence the neuromuscular reflex, eventually altering the reaction time for dorsiflexion [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate force control of the ankle requires the proper functioning of baroreceptors and the regulation of cortical networks of the brain [ 51 ]. A single session of HD-tDCS applied over SM1 enhanced force control by modulating the beta-band activity of the sensorimotor cortex [ 23 ]. Moreover, tDCS can modulate cortical excitability to influence the neuromuscular reflex, eventually altering the reaction time for dorsiflexion [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…tDCS also modulated corticospinal excitability in the lower limb region of the motor cortex and enhanced foot biomechanical performance [ 24 , 27 ]. Our recent findings suggested that participants exhibited a greater average percent decrease in beta task-related power spectral density (i.e., greater cortical activation) following a greater percent reduction in the root mean square of force control task (i.e., greater improvement in ankle force control task) after application of HD-tDCS; hence, HD-tDCS could modulate beta-band brain activity to improve ankle force control task [ 23 ]. Regarding improvements in foot neuro-biomechanical function, existing research suggests that tDCS primarily enhances excitability in the primary sensory cortex (S1).…”
Section: Discussionmentioning
confidence: 99%